2021
DOI: 10.31557/apjcp.2021.22.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Never Screened with Faecal Occult Blood Test in Public Primary Care Facilities

Abstract: that 5 years survival of CRC in Malaysian patients is about 40%, which is lower than the high income countries such as Singapore (60%) and South Korea (73%) (Veettil et al., 2017). Furthermore, malignant tumour is among five top causes of death among Malaysian and increasing in trend for the past 20 years, accounts for 8.6% on 1996 and 13.6% deaths on 2015 in Malaysians hospitals (Ministry Abstract Background: Colorectal cancer (CRC) is still a major public health threat. In the effort to reduce CRC incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Another reason for a lower overall survival in this study could be due to the unavailability of populationbased colorectal screening program which was yet to be implemented during the study period (Chandran et al, 2020;Ministry of Health Malaysia, 2012). It was proven that the diagnosis through community-based screening program had led to early stage at diagnosis, which subsequently had better survival rate, as evidenced in this study and other studies (Abu Aryaie et al, 2013;Ghazali et al, 2010;Kral et al, 2020;Lim et al, 2020;Magaji et al, 2017;Rasouli et al, 2017;Sazali et al, 2021). Screening strategies need to be revisited and may need newer approach such as using smart healthcare delivery to improve access via digital health integration.…”
Section: Discussionsupporting
confidence: 52%
“…Another reason for a lower overall survival in this study could be due to the unavailability of populationbased colorectal screening program which was yet to be implemented during the study period (Chandran et al, 2020;Ministry of Health Malaysia, 2012). It was proven that the diagnosis through community-based screening program had led to early stage at diagnosis, which subsequently had better survival rate, as evidenced in this study and other studies (Abu Aryaie et al, 2013;Ghazali et al, 2010;Kral et al, 2020;Lim et al, 2020;Magaji et al, 2017;Rasouli et al, 2017;Sazali et al, 2021). Screening strategies need to be revisited and may need newer approach such as using smart healthcare delivery to improve access via digital health integration.…”
Section: Discussionsupporting
confidence: 52%
“… 31 , 32 Better mode of communication should be developed which tailored the needs of local community using available infrastructure, especially through the utilization of digital technology and enhancing the role of university’s family health physician in increasing the awareness among students. 33 , 34…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was estimated using a single mean formula for hypothesis testing. A total of 567 respondents was required in this study with the assumed study population’ standard deviation of 3.4 [ 33 ], 95% confidence interval and desired precision of 0.3.…”
Section: Design and Methodsmentioning
confidence: 99%
“…However, study on the acceptance of CRC screening in Malaysia is limited. A recent study performed in Sabah, Malaysia recorded a prevalence of 85.8% population that has never been screened by FOBT [43]. Another study among average risk individuals in West Malaysia found that there were only 13 respondents or 0.7% (out of 1905 respondents) that have been screened for CRC [44].…”
Section: Uptake Of Crc Screeningmentioning
confidence: 99%
“…A recent study performed in Sabah, Malaysia recorded a prevalence of 85.8% population that has never been screened by FOBT. 43 Another study among average risk individuals in West Malaysia found that there were only 13 respondents or 0.7% (out of 1905 respondents) that have been screened for CRC. 44 In a multicentre study in the Asia Pacific region, Malaysia recorded among the highest prevalence with poor participation of CRC screening (97%) compared to another country in the same region such as the Philippines (31%), Japan (62%), and Brunei (86.3%).…”
Section: Uptake Of Crc Screeningmentioning
confidence: 99%